The Correlation Between Students' Reading Habit and Students' Reading Comprehension at the Eighth Grade of SMP Negeri 3 Kramatwatu - Sintawati, Fairus; Azzahro, Nisa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
Reading comprehension and reading habit are two interrelated and inseparable concepts. Reading comprehension is the foundation of reading. The purpose of this study is to answer the problem of how the correlation of reading habits with the reading ability of junior high school students. This research took place in SMP Negeri 3 Kramatwatu. This study uses a quantitative approach by using survey research methods used through SPSS statistical tests. The instruments used in this study are reading habit questionnaire and reading comprehension test. The population in this study were all VIII grade students of SMP Negeri 3 Kramatwatu which amounted to 258 students. The sample used was 32 students with the sampling technique used was Simple Random Sampling. The results of this study indicate a correlation between students' reading habits and reading ability. The results of statistical analysis using the product moment correlation formula indicate that the rcount value is equal to 0.793 and the rtable at a significant level of 0.05 is 0.349, then rcount > rtable. So that rcount is greater than rtable, it can be concluded that the Ho hypothesis is rejected and H1 is accepted. This shows that students' reading habits are one of the components that determine students' reading comprehension.